Social Policy of Ukraine: State and Prospects (Economic journal of Lesya Ukrainka Volyn National University, 2017)
In the article «Social policy: the state and prospects of development» Dmitry Valerievich Makhovskiy, the modern state of the social sphere, the regulatoryand legal framework, the influence of various factors and institutions on its development, and the state and prospects for the development of social policy in Ukraine are analyzed. The article analyzes new trends in social policy in the modern world. The composition of subjects of social policy is specified. The essence of social policy as the activity of the state and other social institutions in the social sphere is considered. The peculiarities of the orientation of social policy under the conditions of globalization processes and the formation of modern knowledge-based economies are studied. The analysis of the state of social policy in Ukraine is made, the causal relationships and regularities of the socioeconomic crisis in Ukraine and possible ways to overcome it are identified, the main problem phenomena are identified and the principles for further reform are proposed. Underlined the lack of system in the implementation ofsocial policy in the country, the lack of its short-term and strategic forecasting and planning.
Keywords: social policy, social security, subsistence minimum, minimum wage, minimum pension, state social standards, social guarantees, social services